2016
DOI: 10.3390/ma9120979
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biowaste Asian Hard Clam (Meretrix lusoria) Shells into White-Emitting Phosphors for Use in Neutral White LEDs

Abstract: The increasing volume and complexity of waste associated with the modern economy poses a serious risk to ecosystems and human health. However, the remanufacturing and recycling of waste into usable products can lead to substantial resource savings. In the present study, clam shell waste was first transformed into pure and well-crystallized single-phase white light-emitting phosphor Ca9Gd(PO4)7:Eu2+,Mn2+ materials. The phosphor Ca9Gd(PO4)7:Eu2+,Mn2+ materials were synthesized by the solid-state reaction method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Comparing the XRD patterns of the original WWSSP and the TWWSSP prepared at 500 °C (Figure b) indicates that there are two new peaks at about 17.9° (1) and 34.2° (2), respectively. This result is consistent with partial decomposition of CaCO 3 into Ca­(OH) 2 during the thermal treatment of WWSSP at 500 °C . Compared with Figure c, seven new peaks are apparent at 28.6° (3), 32.1° (4), 34.5° (5), 37.2° (6), 47.3° (7), 50.7° (8), and 53.8° (9) in the XRD pattern of the TWWSSP formed at 1000 °C (Figure c).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Comparing the XRD patterns of the original WWSSP and the TWWSSP prepared at 500 °C (Figure b) indicates that there are two new peaks at about 17.9° (1) and 34.2° (2), respectively. This result is consistent with partial decomposition of CaCO 3 into Ca­(OH) 2 during the thermal treatment of WWSSP at 500 °C . Compared with Figure c, seven new peaks are apparent at 28.6° (3), 32.1° (4), 34.5° (5), 37.2° (6), 47.3° (7), 50.7° (8), and 53.8° (9) in the XRD pattern of the TWWSSP formed at 1000 °C (Figure c).…”
Section: Resultsmentioning
confidence: 73%
“…This result is consistent with partial decomposition of CaCO 3 into Ca(OH) 2 during the thermal treatment of WWSSP at 500 °C. 32 Compared with Figure 1c, seven new peaks are apparent at 28.6°(3), 32.1°( 4), 34.5°(5), 37.2°(6), 47.3°(7), 50.7°(8), and 53.8°(9) in the XRD pattern of the TWWSSP formed at 1000 °C (Figure 1c). These results indicate that increasing the calcination temperature to 1000 °C led to complete transformation of WWSSP from CaCO 3 to CaO and Ca(OH) 2 33,34 with simultaneous CO 2 release.…”
Section: Characterization Of White Scallop Shell Powdermentioning
confidence: 75%
“…The highest intensity peaks of clamshell are found at 2θ = 26.16°. XRD patterns of the clam shells patterns are matches with the aragonite form (JCPDS 41–1475) (Chang et al , 2016). Hence, it is concluded that the aragonite, polymorphous structure of CaCO 3 is present in the clam shell powder.…”
Section: Methodsmentioning
confidence: 73%